MgB2 superconducting material and preparation method thereof
By using C-PDA to coat B powder as the precursor powder, the C doping efficiency of MgB2 material is improved, and the problem of low critical current density performance of MgB2 wires at high fields is solved, and a higher transmission critical current density is achieved.
Patent Information
- Application Number
- CN202510030469.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-28
AI Technical Summary
The existing MgB2 wires have low critical current density (Jc) performance at high field, limiting their application range.
C-PDA-coated B powder is used as the precursor powder, and polydopamine-coated boron powder is coated with boron powder or carbide polydopamine-coated boron powder to improve the C doping efficiency and reduce the boron-rich region, thereby increasing the transmission critical current density of MgB2 materials under high fields.
The critical current density of MgB2 materials at high fields is significantly improved, which is better than the performance of existing commercial MgB2 materials.
Smart Images

Figure CN119724735A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of superconducting material preparation, and specifically relates to a MgB2 superconducting material and a preparation method thereof. Background Art
[0002] In 2001, MgB2 was used as a superconducting transition temperature (T c ) Superconducting materials up to 39 K are well known. Compared with traditional NbTi and Nb3Sn superconducting materials, MgB2 has a higher T c This allows it to work in a liquid helium-free environment (20 K). In addition, MgB2 has a higher upper critical field (H c2 ) and critical current density (J c ), there is no weak connection effect of grains; at the same time, the raw materials for preparing MgB2 are abundant and low in cost. Therefore, MgB2 is considered to be the most suitable wire / ribbon material for superconducting magnets in medical magnetic resonance imaging (MRI) used at refrigerator operating temperatures.
[0003] However, the intrinsic magnetic flux pinning of pure MgB2 is weak, which leads to the c As the external magnetic field increases, it decays rapidly, limiting its application under high fields. Studies have found that by doping MgB2 with C, the superconducting properties of samples under high fields can be effectively improved. C replaces the B position in the MgB2 lattice, causing lattice distortion and significantly improving the flux pinning ability of MgB2. At the same time, the lattice C replacing the B position contributes additional electrons, enhancing intraband electron scattering and further increasing the upper critical field (H) of MgB2. c2 ) and the irreversible field (H irr ).
[0004] The current MgB2 wire mainly uses C-coated B powder as the precursor powder of C-doped MgB2. (For example, Hyper TechResearch, Inc. (HTR) uses C-coated B powder prepared by Specialty Materials Inc. (SMI) to prepare MgB2 wire, and Western Superconducting uses C-coated B powder prepared by Pavezyum Company (PVZ) to prepare MgB2 wire.) The C-doped MgB2 wire prepared in this way greatly improves the high-field J c The dense C layer formed by the current C-coated B powder will inhibit the reaction between Mg and B, resulting in a large number of boron-rich regions in the MgB2 reaction layer after heat treatment, which reduces the engineering critical current density (J c ). The performance of commercial MgB2 wire at 4.2 K and 10 T is very low. c Less than 4×10 4 A / cm2 Therefore, a method is needed to improve the performance of MgB2 materials. Summary of the invention
[0005] In order to solve the above problems, the present invention proposes a method for preparing a MgB2 superconducting material. The precursor powder of the superconducting material is coated with B powder by C-PDA to prepare a C-uniformly doped MgB2 wire.
[0006] Another object of the present invention is to provide a MgB2 superconducting material prepared by the above-mentioned method for preparing the MgB2 superconducting material.
[0007] The present invention achieves the above-mentioned invention object through the following technical solutions:
[0008] A method for preparing a MgB2 superconducting material, the method comprising the following steps:
[0009] Step 1: Powder filling: Put the Mg rod into the sheath, fill the space between the sheath and the Mg rod with precursor powder, and compact and seal the sheath to obtain the sheath filled with precursor powder;
[0010] Step 2: cold working; cold working the sheath filled with precursor powder obtained in step 1 to obtain a MgB2 single-core IMD wire;
[0011] Step 3: heat treatment: heat treating the MgB2 single-core IMD wire obtained in step 2;
[0012] The precursor powder is polydopamine-coated boron powder or carbonized polydopamine-coated boron powder.
[0013] The density of the precursor powder in step 1 is 0.6-0.7 g / cm 3 .
[0014] Wherein, the polydopamine-coated boron powder is prepared by the following method:
[0015] Step 01: Disperse the boron powder evenly in the solvent, then add tromethamine to completely dissolve it, and then add dopamine. After a certain period of reaction, separate the powder, and dry the powder to obtain polydopamine-coated boron powder.
[0016] Wherein, the carbonized polydopamine-coated boron powder is prepared by the following method:
[0017] Step 01: Disperse the boron powder evenly in a solvent, then add tromethamine to completely dissolve it, and then add dopamine. After a certain period of reaction, separate the powder, and dry the powder to obtain polydopamine-coated boron powder;
[0018] Step 02: Carbonizing the polydopamine-coated boron powder to obtain carbonized powder;
[0019] Step 03: The carbonized powder is cleaned, separated and dried to obtain carbonized polydopamine-coated boron powder.
[0020] The reaction time of step 01 is more than 4 h.
[0021] Wherein, the mass ratio of the boron powder to the dopamine in step 01 is 1:0.5-1.5;
[0022] The mass volume concentration of the boron powder and the solvent is 0.5-2 mg / mL;
[0023] The mass ratio of the tromethamine to the dopamine is 1-3:1.
[0024] Wherein, the temperature of the carbonization treatment is 900-1000°C, and the time of the carbonization treatment is ≥5 h.
[0025] The carbonization treatment is carried out under vacuum, and the vacuum degree is less than 10 -3 Pa.
[0026] The MgB2 superconducting material is prepared by the above-mentioned method for preparing the MgB2 superconducting material.
[0027] The beneficial effects of the present invention are as follows:
[0028] (1) The present invention proposes a new MgB2 superconducting material, the critical current density (J c ) performance is better than the existing commercial MgB2 material. The spontaneous polymerization of dopamine in alkaline buffer is used to form a polydopamine coating on the surface of B powder. After high-temperature carbonization treatment, C-PDA-coated B powder is formed; using C-PDA-coated B powder as precursor powder, the wire prepared by the central magnesium diffusion method (IMD) has excellent superconducting performance.
[0029] (2) The preparation method of the present invention uses polydopamine (PDA) coated boron (B) powder or carbonized polydopamine (C-PDA) coated boron (B) powder as the precursor powder of MgB2 superconducting material; a large amount of organic active C on the surface of C-PDA coated B powder enhances the reaction activity of coated B powder and improves C doping efficiency, and finally effectively reduces the boron-rich region of the MgB2 reaction layer, thereby improving the transmission critical current density (J) of MgB2 material under high field. c ). BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the EDS energy spectrum of the precursor powder (polydopamine-coated boron powder) prepared in Example 2.
[0031] Figure 2 This is the EPMA spectrum of the MgB2 superconducting material prepared in Example 2. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0033] The preparation method of the above-mentioned MgB2 superconducting material uses polydopamine-coated boron powder or carbonized polydopamine-coated boron powder as precursor powder; the preparation method comprises the following steps:
[0034] Step 1: Powder tube filling: put the Mg rod into the wire sheath, tightly fill the carbonized polydopamine-coated boron powder between the sheath and the Mg rod, and compact and seal it to obtain a sheath filled with precursor powder; the sheath can be a wire sheath or a strip sheath;
[0035] Step 2: cold working; cold working the wire sheath filled with precursor powder obtained in step 1 to obtain MgB2 single-core IMD wire; the cold working treatment includes rotary forging, drawing, etc. Specifically, the wire sheath filled with precursor powder is rotary forged to a certain diameter; and then drawn to the required diameter; rotary forging adopts a processing rate of 10-20% per pass, and drawing adopts a surface reduction rate of 8-10% per pass;
[0036] Step 3: heat treatment: heat treatment is performed on the MgB2 single-core IMD wire obtained in step 2. The heat treatment is performed by sintering under the condition of flowing inert gas; during the sintering process, the heating rate is 3-10 °C / min, the heat treatment temperature is 580-700 °C, and the holding time is 1.5-10 h.
[0037] The packing density of the carbonized polydopamine-coated boron powder in step 1 is 0.6-0.7 g / cm 3 .
[0038] Preferably, the polydopamine-coated boron powder is prepared by the following method:
[0039] Step 01: Disperse the boron powder evenly in a solvent, then add tromethamine to completely dissolve it, and then add dopamine. After a certain period of reaction, separate the powder, and dry the powder to obtain polydopamine-coated boron powder. The solvent in the present invention is methanol or N,N-dimethylformamide (DMF). The present invention adopts ultrasonic dispersion to make it evenly dispersed, and the reaction is carried out under stirring. The drying temperature of the powder is >100 °C and the drying time is >6 h.
[0040] Preferably, the carbonized polydopamine-coated boron powder is prepared by the following method:
[0041] Step 01: Disperse the boron powder evenly in a solvent, then add tromethamine to completely dissolve it, then add dopamine, and after a certain period of reaction, separate the powder, and dry the powder to obtain polydopamine-coated boron powder; the solvent in the present invention is methanol or N,N-dimethylformamide (DMF); the present invention adopts ultrasonic dispersion to make it evenly dispersed, the reaction is carried out under stirring, the powder is dried at a temperature of>100°C, and the drying time is>6 h;
[0042] Step 02: Carbonizing the polydopamine-coated boron powder to obtain carbonized powder;
[0043] Step 03: The carbonized powder is cleaned, separated and dried to obtain carbonized polydopamine-coated boron powder.
[0044] The reaction time of step 01 is 24 h.
[0045] Wherein, the mass ratio of the boron powder to the dopamine is 1:0.5-1.5;
[0046] The mass volume concentration of the boron powder and the solvent is 0.5-2 mg / mL;
[0047] The amount of tromethamine added is 1 to 3 times the mass of PDA.
[0048] Wherein, the temperature of the carbonization treatment is 900-1000°C, and the time of the carbonization treatment is ≥5 h.
[0049] The carbonization treatment is carried out under vacuum, and the vacuum degree is less than 10 -3 Pa.
[0050] Example 1
[0051] In this embodiment, Fe-sheathed MgB2 single-core IMD wire is prepared, and polydopamine (PDA)-coated boron (B) powder is used as precursor powder.
[0052] The preparation process of Fe-sheathed MgB2 single-core IMD wire is as follows:
[0053] Step 1, powder tube. Prepare a 9×6 mm Fe tube as the wire sheath. In a glove box with Ar gas protection atmosphere, place a Mg rod with a diameter of Φ 4 mm into the Fe tube, fill the space between the sheath and the Mg rod with PDA-coated B powder, and compact and seal it. The tube density of B powder is guaranteed to be 0.6 ~ 0.7 g / cm 3 .
[0054] Step 2: Cold working of the wire. The Fe rod filled with precursor powder is first rotary forged to Φ 5 mm and then drawn to Φ 1.2 mm to prepare the MgB2 single-core IMD wire. The rotary forging adopts a processing rate of 15% per pass, and the drawing adopts a surface reduction rate of 10% per pass.
[0055] Step 3, heat treatment of wire. The prepared single-core wire is placed in a tubular furnace with flowing argon for sintering. During the sintering process, the sample heating rate is 5 ℃ / min, the heat treatment temperature is 650 ℃, and the holding time is 5 h. After high-temperature heat treatment, high-performance MgB2 single-core wire can be prepared. After testing, it is known that the transmission critical current density of the wire is 5.9×10 4 A / cm 2 (4.2 K, 10 T).
[0056] The PDA-coated B powder used in this embodiment was prepared by the following method:
[0057] Step 01: Prepare polydopamine (PDA) coated B powder.
[0058] Take 500 mg of PVZ nanopowder B and place it in 1 L of methanol solvent. Ultrasonicate the solution for 4 h to completely disperse the powder B in the methanol solvent. After the powder B is evenly dispersed, dissolve 1000 mg of tromethamine (C4H 11 NO3) as a buffer, and ultrasonicate for 1 h again to completely dissolve the buffer. After that, 500 mg of dopamine was dissolved in the solution as a coating source. The entire solution was exposed to air and reacted for 24 h using magnetic stirring. The reacted solution was filtered and separated using a 22μm porous filter membrane to obtain the PDA-coated B powder. Finally, it was dried in a vacuum oven at 160°C for 10 h to obtain the PDA-coated B powder.
[0059] Example 2
[0060] In this embodiment, Fe-sheathed MgB2 single-core IMD wire is prepared, and carbonized polydopamine (C-PDA)-coated boron (B) powder is used as precursor powder.
[0061] The preparation steps are as follows:
[0062] Step 1: Powder tube. Prepare a 9×6 mm Fe tube as the wire sheath. In a glove box with Ar gas protection atmosphere, place a Mg rod with a diameter of Φ 4 mm into the Fe tube, tightly fill the space between the sheath and the Mg rod with C-PDA-coated B powder, and compact and seal it. The tube density of B powder is guaranteed to be 0.6 ~ 0.7 g / cm 3 .
[0063] Step 2: Cold working of the wire. The Fe rod filled with precursor powder is first rotary forged to Φ 5 mm and then drawn to Φ 1.2 mm to prepare the MgB2 single-core IMD wire. The rotary forging adopts a processing rate of 15% per pass, and the drawing adopts a surface reduction rate of 10% per pass.
[0064] Step 3, heat treatment of the wire. The prepared single-core wire is placed in a tubular furnace with flowing argon for sintering. During the sintering process, the sample heating rate is 5 ℃ / min, the heat treatment temperature is 650 ℃, and the holding time is 5 h. After high-temperature heat treatment, high-performance MgB2 single-core wire can be prepared. After testing, it is known that the transmission critical current density (J c ) is 8.0×10 4 A / cm 2 (4.2 K, 10 T).
[0065] The C-PDA coated B powder used in this example was prepared by the following method:
[0066] Step 01: Prepare polydopamine (PDA) coated B powder.
[0067] Take 500 mg of nano B powder (purchased from PVZ) and place it in 1 L of methanol solvent. Ultrasonicate the solution for 4 h to completely disperse the B powder in the methanol solvent. After the B powder is evenly dispersed, dissolve 1000 mg of tromethamine (C4H 11 NO3) as a buffer, and ultrasonicate for 1 h again to completely dissolve the buffer. After that, 500 mg of dopamine was dissolved in the solution as a coating source. The entire solution was exposed to air and reacted for 24 h using magnetic stirring. The reacted solution was filtered and separated using a 22 μm porous filter membrane to obtain the PDA-coated B powder. Finally, it was dried in a vacuum oven at 160 °C for 10 h to obtain the PDA-coated B powder.
[0068] Step 02: Prepare carbonized polydopamine (C-PDA) coated B powder.
[0069] 500 mg of PDA-coated B powder was placed in a graphite boat and placed in a tube furnace for carbonization heat treatment. The heat treatment temperature was 900 °C, the heat treatment time was 5 h, and the atmosphere was vacuum treated;
[0070] Step 03: After high-temperature carbonization, the powder was re-dissolved in 1 L of ethanol solvent, and the powder was cleaned by ultrasonic and magnetic stirring to remove impurities (B2O3, uncarbonized PDA) in the powder. The cleaned powder was separated by filtration and dried in a vacuum oven at 160 °C for 10 h to obtain C-PDA-coated B powder.
[0071] Figure 1 This is the EDS spectrum of carbonized polydopamine (C-PDA) coated B powder. Figure 1 It can be seen that PDA is evenly coated on the surface of B powder to form a C shell. Figure 2 This is the EPMA spectrum of MgB2 wire prepared by C-PDA coated B powder. Figure 2 The EPMA graph shows that C is evenly distributed in the superconducting layer, forming uniform C-doped MgB2.
[0072] Example 3
[0073] In this embodiment, Fe-sheathed MgB2 single-core IMD wire is prepared, and carbonized polydopamine (C-PDA)-coated boron (B) powder is used as precursor powder.
[0074] The preparation steps are as follows:
[0075] The first step is to pack the powder into a tube. Prepare a 9×6 mm Fe tube as the wire sheath. In a glove box with an Ar gas atmosphere, place a Mg rod with a diameter of Φ 4 mm into the Fe tube, fill the space between the sheath and the Mg rod with C-PDA-coated B powder, and compact and seal it. The tube density of B powder is guaranteed to be between 0.6 and 0.7 g / cm 3 .
[0076] The second step is cold processing of the wire. The Fe rod filled with precursor powder is first forged to Φ 5 mm, and then drawn to Φ 1.2 mm to prepare the MgB2 single-core IMD wire. The forging process uses a processing rate of 15% per pass, and the drawing process uses a surface reduction rate of 10% per pass.
[0077] The third step is heat treatment of the wire. The prepared single-core wire is placed in a tubular furnace with flowing argon for sintering. During the sintering process, the sample heating rate is 5 ℃ / min, the heat treatment temperature is 650 ℃, and the holding time is 5 h. After high-temperature heat treatment, high-performance MgB2 single-core wire can be prepared. After testing, it is known that the transmission critical current density of the wire is 8.6×10 4 A / cm 2 (4.2 K, 10 T).
[0078] The C-PDA coated B powder used in this example was prepared by the following method:
[0079] Step 01: Prepare polydopamine (PDA) coated B powder.
[0080] Take 500 mg of nano B powder (purchased from PVZ) and place it in 1 L of methanol solvent. Ultrasonicate the solution for 4 h to completely disperse the B powder in the methanol solvent. When the B powder is evenly dispersed, dissolve 1400 mg of tromethamine (C4H 11 NO3) as a buffer, and ultrasonicate for 1 h again to completely dissolve the buffer. After that, 700 mg of dopamine was dissolved in the solution as a coating source. The entire solution was exposed to air and reacted for 24 h using magnetic stirring. The reacted solution was filtered and separated using a 22 μm porous filter membrane to obtain the PDA-coated B powder. Finally, it was dried in a vacuum oven at 160 °C for 10 h to obtain the PDA-coated B powder.
[0081] Step 02: Prepare carbonized polydopamine (C-PDA) coated B powder.
[0082] 500 mg of PDA-coated B powder was placed in a graphite boat and placed in a tube furnace for carbonization heat treatment. The heat treatment temperature was 900 °C, the drying time was 5 h, and the atmosphere was vacuum treated.
[0083] Step 03: After high-temperature carbonization, the powder was re-dissolved in 1 L of ethanol solvent, and the powder was cleaned by ultrasonic and magnetic stirring to remove impurities (B2O3, uncarbonized PDA) in the powder. The cleaned powder was separated by filtration and dried in a vacuum oven at 160 °C for 10 h to obtain C-PDA-coated B powder.
[0084] Example 4
[0085] In this embodiment, Fe-sheathed MgB2 single-core IMD wire is prepared, and carbonized polydopamine (C-PDA)-coated boron (B) powder is used as precursor powder.
[0086] The preparation steps are as follows:
[0087] The first step is to pack the powder into a tube. Prepare a 9×6 mm Fe tube as the wire sheath. In a glove box with an Ar gas atmosphere, place a Mg rod with a diameter of Φ 4 mm into the Fe tube, fill the space between the sheath and the Mg rod with C-PDA-coated B powder, and compact and seal it. The tube density of B powder is guaranteed to be between 0.6 and 0.7 g / cm 3 .
[0088] The second step is cold processing of the wire. The Fe rod filled with precursor powder is first forged to Φ 5 mm, and then drawn to Φ 1.2 mm to prepare the MgB2 single-core IMD wire. The forging process uses a processing rate of 15% per pass, and the drawing process uses a surface reduction rate of 10% per pass.
[0089] The third step is heat treatment of the wire. The prepared single-core wire is placed in a tubular furnace with flowing argon for sintering. During the sintering process, the sample heating rate is 5 ℃ / min, the heat treatment temperature is 650 ℃, and the holding time is 5 h. After high-temperature heat treatment, high-performance MgB2 single-core wire can be prepared. After testing, it is known that the transmission critical current density of the wire is 4.92×10 4 A / cm 2 (4.2 K, 10 T).
[0090] The C-PDA coated B powder used in this example was prepared by the following method:
[0091] Step 01: Prepare polydopamine (PDA) coated B powder.
[0092] Take 500 mg of nano B powder (purchased from PVZ) and place it in 1 L of methanol solvent. Ultrasonicate the solution for 4 h to completely disperse the B powder in the methanol solvent. After the B powder is evenly dispersed, dissolve 600 mg of tromethamine (C4H 11 NO3) as a buffer, and ultrasonicate for 1 h again to completely dissolve the buffer. After that, 300 mg of dopamine was dissolved in the solution as a coating source. The entire solution was exposed to air and reacted for 24 h using magnetic stirring. The reacted solution was filtered and separated using a 22 μm porous filter membrane to obtain the PDA-coated B powder. Finally, it was dried in a vacuum oven at 160 °C for 10 h to obtain the PDA-coated B powder.
[0093] Step 02: Prepare carbonized polydopamine (C-PDA) coated B powder.
[0094] 500 mg of PDA-coated B powder was placed in a graphite boat and placed in a tube furnace for carbonization heat treatment. The heat treatment temperature was 900 °C, the drying time was 5 h, and the atmosphere was vacuum treated.
[0095] Step 03: After high-temperature carbonization, the powder was re-dissolved in 1 L of ethanol solvent, and the powder was cleaned by ultrasonic and magnetic stirring to remove impurities (B2O3, uncarbonized PDA) in the powder. The cleaned powder was separated by filtration and dried in a vacuum oven at 160 °C for 10 h to obtain C-PDA-coated B powder.
[0096] Example 5
[0097] In this embodiment, Fe-sheathed MgB2 single-core IMD wire is prepared, and carbonized polydopamine (C-PDA)-coated boron (B) powder is used as precursor powder.
[0098] The preparation steps are as follows:
[0099] The first step is to pack the powder into a tube. Prepare a 9×6 mm Fe tube as the wire sheath. In a glove box with an Ar gas atmosphere, place a Mg rod with a diameter of Φ 4 mm into the Fe tube, fill the space between the sheath and the Mg rod with C-PDA-coated B powder, and compact and seal it. The tube density of B powder is guaranteed to be between 0.6 and 0.7 g / cm 3 .
[0100] The second step is cold processing of the wire. The Fe rod filled with precursor powder is first forged to Φ 5 mm, and then drawn to Φ 1.2 mm to prepare the MgB2 single-core IMD wire. The forging process uses a processing rate of 15% per pass, and the drawing process uses a surface reduction rate of 10% per pass.
[0101] The third step is heat treatment of the wire. The prepared single-core wire is placed in a tubular furnace with flowing argon for sintering. During the sintering process, the sample heating rate is 5 ℃ / min, the heat treatment temperature is 650 ℃, and the holding time is 5 h. After high-temperature heat treatment, high-performance MgB2 single-core wire can be prepared. After testing, it is known that the transmission critical current density of the wire is 6.06×10 4 A / cm 2 (4.2 K, 10 T).
[0102] The C-PDA coated B powder used in this example was prepared by the following method:
[0103] Step 01: Prepare polydopamine (PDA) coated B powder.
[0104] Take 500 mg of nano B powder (purchased from PVZ) and place it in 1 L of methanol solvent. Ultrasonicate the solution for 4 h to completely disperse the B powder in the methanol solvent. After the B powder is evenly dispersed, dissolve 1800 mg of tromethamine (C4H 11 NO3) as a buffer, and ultrasonicate for 1 h again to completely dissolve the buffer. After that, 900 mg of dopamine was dissolved in the solution as a coating source. The entire solution was exposed to air and reacted for 24 h using magnetic stirring. The reacted solution was filtered and separated using a 22 μm porous filter membrane to obtain the PDA-coated B powder. Finally, it was dried in a vacuum oven at 160 °C for 10 h to obtain the PDA-coated B powder.
[0105] Step 02: Prepare carbonized polydopamine (C-PDA) coated B powder.
[0106] 500 mg of PDA-coated B powder was placed in a graphite boat and placed in a tube furnace for carbonization heat treatment. The heat treatment temperature was 900 °C, the drying time was 5 h, and the atmosphere was vacuum treated.
[0107] Step 03: After high-temperature carbonization, the powder was re-dissolved in 1 L of ethanol solvent, and the powder was cleaned by ultrasonic and magnetic stirring to remove impurities (B2O3, uncarbonized PDA) in the powder. The cleaned powder was separated by filtration and dried in a vacuum oven at 160 °C for 10 h to obtain C-PDA-coated B powder.
[0108] Example 6
[0109] In this embodiment, Fe-sheathed MgB2 single-core IMD wire is prepared, and carbonized polydopamine (C-PDA)-coated boron (B) powder is used as precursor powder.
[0110] The preparation steps are as follows:
[0111] The first step is to pack the powder into a tube. Prepare a 9×6 mm Fe tube as the wire sheath. In a glove box with an Ar gas atmosphere, place a Mg rod with a diameter of Φ 4 mm into the Fe tube, fill the space between the sheath and the Mg rod with C-PDA-coated B powder, and compact and seal it. The tube density of B powder is guaranteed to be between 0.6 and 0.7 g / cm 3 .
[0112] The second step is cold processing of the wire. The Fe rod filled with precursor powder is first forged to Φ 5 mm, and then drawn to Φ 1.2 mm to prepare the MgB2 single-core IMD wire. The forging process uses a processing rate of 10% per pass, and the drawing process uses an area reduction rate of 8% per pass.
[0113] The third step is heat treatment of the wire. The prepared single-core wire is placed in a tubular furnace with flowing argon for sintering. During the sintering process, the sample heating rate is 3 ℃ / min, the heat treatment temperature is 580 ℃, and the holding time is 6 h. After high-temperature heat treatment, high-performance MgB2 single-core wire can be prepared.
[0114] The C-PDA coated B powder used in this example was prepared by the following method:
[0115] Step 01: Prepare polydopamine (PDA) coated B powder.
[0116] Take 500 mg of nano B powder (purchased from PVZ) and place it in 250 mL of methanol solvent. Ultrasonicate the solution for 4 h to completely disperse the B powder in the methanol solvent. After the B powder is evenly dispersed, dissolve 250 mg of tromethamine (C4H 11 NO3) as a buffer, and ultrasonicate for 1 h again to completely dissolve the buffer. After that, 250 mg of dopamine was dissolved in the solution as a coating source. The entire solution was exposed to air and reacted for 24 h using magnetic stirring. The reacted solution was filtered and separated using a 22 μm porous filter membrane to obtain the PDA-coated B powder. Finally, it was dried in a vacuum oven at 200 °C for 8 h to obtain the PDA-coated B powder.
[0117] Step 02: Prepare carbonized polydopamine (C-PDA) coated B powder.
[0118] 500 mg of PDA-coated B powder was placed in a graphite boat and placed in a tube furnace for carbonization heat treatment. The heat treatment temperature was 1000 °C, the drying time was 6 h, and the atmosphere was vacuum treated.
[0119] Step 03: After high-temperature carbonization, the powder was re-dissolved in 1 L of ethanol solvent, and the powder was cleaned by ultrasonic and magnetic stirring to remove impurities (B2O3, uncarbonized PDA) in the powder. The cleaned powder was separated by filtration and dried in a vacuum oven at 180 °C for 10 h to obtain C-PDA-coated B powder.
[0120] Example 7
[0121] In this embodiment, Fe-sheathed MgB2 single-core IMD wire is prepared, and carbonized polydopamine (C-PDA)-coated boron (B) powder is used as precursor powder.
[0122] The preparation steps are as follows:
[0123] The first step is to pack the powder into a tube. Prepare a 9×6 mm Fe tube as the wire sheath. In a glove box with an Ar gas atmosphere, place a Mg rod with a diameter of Φ 4 mm into the Fe tube, fill the space between the sheath and the Mg rod with C-PDA-coated B powder, and compact and seal it. The tube density of B powder is guaranteed to be between 0.6 and 0.7 g / cm 3 .
[0124] The second step is cold processing of the wire. The Fe rod filled with precursor powder is first forged to Φ 5 mm, and then drawn to Φ 1.2 mm to prepare the MgB2 single-core IMD wire. The forging process uses a processing rate of 20% per pass, and the drawing process uses a surface reduction rate of 10% per pass.
[0125] The third step is heat treatment of the wire. The prepared single-core wire is placed in a tubular furnace with flowing argon for sintering. During the sintering process, the sample heating rate is 10 ℃ / min, the heat treatment temperature is 700 ℃, and the holding time is 3.5 h. After high-temperature heat treatment, high-performance MgB2 single-core wire can be prepared.
[0126] The C-PDA coated B powder used in this example was prepared by the following method:
[0127] Step 01: Prepare polydopamine (PDA) coated B powder.
[0128] Take 500 mg of nano B powder (purchased from PVZ) and place it in 500 ml of DMF solvent. Ultrasonicate the solution for 4 h to completely disperse the B powder in the DMF solvent. When the B powder is evenly dispersed, dissolve 1500 mg of tromethamine (C4H 11 NO3) as a buffer, and ultrasonicate again for 1.5 hours to completely dissolve the buffer. After that, 500 mg of dopamine was dissolved in the solution as a coating source. The entire solution was exposed to air and reacted for 24 hours using magnetic stirring. The reacted solution was filtered and separated by using a 22 μm porous filter membrane to obtain PDA-coated B powder. Finally, it was dried in a vacuum oven at 200 °C for 8 hours to obtain PDA-coated B powder.
[0129] Step 02: Prepare carbonized polydopamine (C-PDA) coated B powder.
[0130] 500 mg of PDA-coated B powder was placed in a graphite boat and placed in a tube furnace for carbonization heat treatment. The heat treatment temperature was 950 °C, the drying time was 6 h, and the atmosphere was vacuum treated.
[0131] Step 03: After high-temperature carbonization, the powder was re-dissolved in 1 L of ethanol solvent, and the powder was cleaned by ultrasonic and magnetic stirring to remove impurities (B2O3, uncarbonized PDA) in the powder. The cleaned powder was separated by filtration and dried in a vacuum oven at 170 °C for 9 h to obtain C-PDA-coated B powder.
[0132] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0133] The parts not elaborated in detail in the description of the present invention belong to the known technology in the art. The above embodiments are provided only for the purpose of describing the present invention, and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. Various equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be included in the scope of the present invention.
Claims
1. A method for preparing a MgB2 superconducting material, characterized in that: The preparation method comprises the following steps: Step 1: Powder filling: Put the Mg rod into the sheath, fill the space between the sheath and the Mg rod with precursor powder, and compact and seal the sheath to obtain the sheath filled with precursor powder; Step 2: cold working; cold working the sheath filled with precursor powder obtained in step 1 to obtain a MgB2 single-core IMD wire; Step 3: heat treatment: heat treating the MgB2 single-core IMD wire obtained in step 2; The precursor powder is polydopamine-coated boron powder or carbonized polydopamine-coated boron powder.
2. The preparation method according to claim 1, characterized in that: The tube density of the precursor powder in step 1 is 0.6~0.7g / cm 3 .
3. The preparation method according to claim 1, characterized in that: The polydopamine-coated boron powder is prepared by the following method: Step 01: Disperse the boron powder evenly in the solvent, then add tromethamine to completely dissolve it, and then add dopamine. After a certain period of reaction, separate the powder, and dry the powder to obtain polydopamine-coated boron powder.
4. The preparation method according to claim 1, characterized in that: The carbonized polydopamine-coated boron powder is prepared by the following method: Step 01: Disperse the boron powder evenly in a solvent, then add tromethamine to completely dissolve it, and then add dopamine. After a certain period of reaction, separate the powder, and dry the powder to obtain polydopamine-coated boron powder; Step 02: Carbonizing the polydopamine-coated boron powder to obtain carbonized powder; Step 03: The carbonized powder is cleaned, separated and dried to obtain carbonized polydopamine-coated boron powder.
5. The preparation method according to claim 3 or 4, characterized in that: The reaction time of step 01 is more than 4 hours.
6. The preparation method according to claim 3 or 4, characterized in that: The mass ratio of the boron powder to the dopamine in step 01 is 1:0.5-1.5; The mass volume concentration of the boron powder and the solvent is 0.5-2 mg / mL; The mass ratio of the tromethamine to the dopamine is 1-3:
1.
7. The preparation method according to claim 4, characterized in that: The temperature of the carbonization treatment is 900-1000°C, and the time of the carbonization treatment is not less than 5 hours.
8. The preparation method according to claim 4, characterized in that: The carbonization treatment is carried out under vacuum, and the vacuum degree is less than 10 -3 Pa.
9. The MgB2 superconducting material prepared by the method for preparing the MgB2 superconducting material according to any one of claims 1 to 8.